SOCIO-PSYCHOLOGICAL OF CHILDREN WITH SPEECH IMPAIRMENT ADAPTATION FEATURES - Maxmudov Xurshid Shuxratovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article details the features of socio-psychological adaptation of children with speech defects, the analysis by scientists of issues of adaptation to changing socio-psychological conditions and the mechanism of adaptation of boalas in preschool age.